2021
DOI: 10.1212/con.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome and Reversible Cerebral Vasoconstriction Syndrome as Syndromes of Cerebrovascular Dysregulation

Abstract: PURPOSE OF REVIEW This article describes the causes, clinical and imaging features, management, and prognosis of posterior reversible encephalopathy syndrome (PRES) and reversible cerebral vasoconstriction syndrome (RCVS), in which the underlying pathophysiology is related to reversible dysregulation of the cerebral vasculature. RECENT FINDINGS PRES and RCVS are descriptive terms, each bringing together conditions with similar clinical-imaging manifesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…An expanding list of possible etiologies of RCVS has been identified [ 2 , 3 , 15 , 17 , 22 ]. Comprehensive reviews can be found elsewhere [ 1 , 23 , 24 ]. Overall, vasoactive substances and post-partum state are the most common secondary causes of RCVS.…”
Section: Clinical Features Significance and Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…An expanding list of possible etiologies of RCVS has been identified [ 2 , 3 , 15 , 17 , 22 ]. Comprehensive reviews can be found elsewhere [ 1 , 23 , 24 ]. Overall, vasoactive substances and post-partum state are the most common secondary causes of RCVS.…”
Section: Clinical Features Significance and Impactmentioning
confidence: 99%
“…Based on the radiological features, dysregulation of cerebral vascular tone has been considered the central element in the pathogenesis of RCVS [ 1 , 23 , 24 ]. An abrupt, unpredictable alteration of central vascular tone associated with excessive sympathetic discharge may explain the cerebral vasoconstriction and, the less mentioned, vasodilatation.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension should also be treated, though specific guidelines regarding target blood pressure and optimal anti-hypertensive have not been established. 15 Experts recommend that fluctuations in blood pressure and hypotension be avoided due to the risk of precipitating cerebral hypoperfusion and secondary ischemia. 15 Treatment of “malignant” forms of PRES may consist of ICU-level care, ventilatory support, treatment of increased ICP, and management of secondary complications including as insertion of EVDs, craniectomy or posterior fossa decompression, and hematoma evacuation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Experts recommend that fluctuations in blood pressure and hypotension be avoided due to the risk of precipitating cerebral hypoperfusion and secondary ischemia. 15 Treatment of “malignant” forms of PRES may consist of ICU-level care, ventilatory support, treatment of increased ICP, and management of secondary complications including as insertion of EVDs, craniectomy or posterior fossa decompression, and hematoma evacuation. 16 No specific guidelines regarding treatment of increased ICP in PRES have been established, and general recommendations regarding the treatment of cerebral edema in neurocritical care patients should be followed, while remaining cognizant of patient’s comorbidities and concomitant diseases.…”
Section: Discussionmentioning
confidence: 99%